An observation of the binder microstructure in WC-(Co+Ru) cemented carbides using transmission Kikuchi diffraction. (1st July 2020) - Eizadjou, Mehdi; Chen, Hansheng; Czettl, Christoph; Pachlhofer, Julia; Primig, Sophie; Ringer, Simon P.
Abstract: The microstructure of WC-(Co+Ru) cemented carbides was studied using transmission Kikuchi diffraction (TKD). We report that the Co FCC grains contain Σ3-annealing twins which undergo an incomplete martensitic transformation to form Co HCP laths on cooling below TMs . The parent Co FCC and product Co HCP phases are related via the Shoji-Nishiyama orientation relationship. Four variants of the Co HCP plates exhibit a special misorientation of 70.5 ± 0.2° 〈 11 2 ¯ 0 〉 . A higher transformed fraction was observed in the sample possessing the lower binder content and finer WC grains. We suggest that this is due to the availability of more WC-binder interfaces, which facilitate Co HCP plate nucleation. Graphical abstract: Image, graphical abstract